2024
DOI: 10.46340/eujem.2024.10.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Net Financial Result of the Activities of the State Enterprises of Ukraine on the Efficiency of the Use of their Capital in the Corporate Management System

Ivan Zayukov,
Hennadii Mazur,
Serhii Kozlovskyi
et al.

Abstract: Increasing the efficiency of corporate management of state-owned enterprises in the current military conditions of Ukraine is an important factor in ensuring an increase in their profitability. The increase in the rate of return on equity is a guarantee of further socio-economic development of state-owned enterprises. The purpose of the article is to study the relationship between the net financial results of the activities of state-owned enterprises and the profitability of their capital as an important task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The authors of this article also support these considerations. Modern studies have also confirmed the thesis of a direct relationship between the level of economic development and migration processes (Kozlovsky & Mazur, 2017;Zayukov et al, 2024). Some contemporary authors, unlike this study, have focused on the economic consequences of migration processes, for example, those occurring in the labour market (Bielewska et al, 2024).…”
Section: Discussionsupporting
confidence: 65%
“…The authors of this article also support these considerations. Modern studies have also confirmed the thesis of a direct relationship between the level of economic development and migration processes (Kozlovsky & Mazur, 2017;Zayukov et al, 2024). Some contemporary authors, unlike this study, have focused on the economic consequences of migration processes, for example, those occurring in the labour market (Bielewska et al, 2024).…”
Section: Discussionsupporting
confidence: 65%
“…In fact, through the training process organised for employees, American companies try to optimise production, achieve the lowest possible costs while maintaining the high quality of the final product (Shpykuliak & Mazur, 2014;Zayukov et al, 2024). Additional requirements include the participation of employees in training sessions where they are taught interpersonal communication.…”
Section: Resultsmentioning
confidence: 99%